Liberia : First and Second Reviews Under the Extended Credit Facility Arrangement, Request for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criteria-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Liberia. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2021)
Restoring macroeconomic stability, providing a foundation for sustainable inclusive growth, and addressing weaknesses in governance remain the main objectives of this program. While allowing for a slight fiscal loosening to meet humanitarian needs during the COVID-19 pandemic, tight monetary policy, much improved public financial management, domestic revenue mobilization, and zero central bank financing have supported the administration's efforts to achieve price and exchange rate stability. This has helped to preserve the purchasing power of the poor who were the most affected by the high inflation environment at the program's inception. The authorities consider bringing the ECF-supported program back on track of utmost importance and are committed to their development plan, the Pro-Poor Agenda for Prosperity and Development (PAPD).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet